Left ventricular remodeling in normotensive Wistar rats exposed to intermittent hypoxia of different duration - Kolesnyk, Yu. M.; Kolesnyk, M. Yu.; Hancheva, O. V.; Isachenko, M. I.; Колесник, Юрій Михайлович; Колесник, Михайло Юрійович; Ганчева, Ольга Вікторівна; Ісаченко, Марія Ігорівна (Запорізький державний медичний університет, 2023)
The aim of the study was to examine cardiotrophin-1, titin, collagen type 1, annexin V and the morphofunctional state of the left ventricle of the heart in experimental rats exposed to intermittent 15-day (IH15) and 60-day hypoxia (IH60). Materials and methods. Intermittent hypoxia was modeled using 30 normotensive male Wistar rats, 7–8 months old, which were randomly assigned to 3 experimental groups of 10 animals each: 1) INT – a control group – intact animals (196.3 ± 6.8 g); 2) IH15 – 15-day hypoxia (205.6 ± 4.1 g); 3) IH60 – 60-day hypoxia (201.1 ± 5.5 g). The study compared the effects of intermittent hypoxia of varying duration: 15-day and 60-day hypoxia. Experimental modeling of intermittent hypoxia of 2 terms revealed a number of differences between the effects dependent on this factor duration through functional (blood pressure measurement, echocardiography) and immunofluorescent studies. Results. Blood pressure in rats of both groups was in the normotensive range, but an increase in systolic by 10 % and diastolic by 19 % was found in IH60 group compared to IH15 group (p < 0.05). In IH15 group, there was a significant decrease in enddiastolic dimension by 20 %, end-systolic dimension by 22 %, an increase in the thickness of left ventricular posterior wall by 44 % and interventricular septum by 33 % as well as left ventricular mass by 12 %, indicating concentric remodeling of the left ventricle, the development of which was confirmed by a 76 % increase in relative wall thickness compared to that in the control group (p < 0.05). Along with these changes, a decrease in end-diastolic volume by 47 %, end-systolic volume by 48 %, stroke volume by 49 % and cardiac output by 50 % with preserved ejection fraction was revealed (p < 0.05). While the parameters of IH60 rats were characterized by an increase in the thickness of interventricular septum by 33 % and left ventricular posterior wall by 17 %, as well as left ventricle mass by 23 %, relative left ventricular wall thickness was 15 % higher than the control value (p < 0.05). At the same time, diastolic volume was 9 % decreased and systolic volume was 24 % increased (p < 0.05). Also, cardiac output was increased by 58 % compared to that in 15-day hypoxic rats with an 8 % decrease in ejection fraction (p < 0.05). The concentrations of markers in IH60 group exceeded those in IH15, namely: cardiotrophin-1 by 39 %, titin by 70 %, collagen type 1 by 60 % and annexin V by 130 % (p < 0.05). Мета роботи – вивчення маркерів кардіотрофіну-1, тайтину, колагену 1 типу, анексину V та морфофункціонального стану лівого шлуночка серця в експериментальних щурів при впливі переривчастої 15- (IH15) та 60-денної гіпоксії (IH60). Матеріали та методи. Для моделювання інтермітуючої гіпоксії використовували 30 нормотензивних щурів-самців лінії Вістар віком 7–8 місяців, яких випадковим чином поділили на 3 експериментальні групи по 10 тварин у кожній: INT – контрольна група – інтактні тварини (196,3 ± 6,8 г); IH15 – 15-добова гіпоксія (205,6 ± 4,1 г); IH60 – 60-денна гіпоксія (201,1 ± 5,5 г). Порівняли наслідки періодичної гіпоксії різної тривалості (15- та 60-денної). Експериментальне моделювання переривчастої гіпоксії 2 термінів виявило низку відмінностей між ефектами, що залежать від тривалості цього фактора, за допомогою функціональних (вимірювання артеріального тиску (АТ), ехокардіографія) та імунофлуоресцентних досліджень. Результати. АТ у щурів обох дослідних груп відповідав нормотензивному діапазону, виявили збільшення систолічного (на 10 %) і діастолічного (на 19 %) тиску в групі IH60 порівняно з IH15 (p < 0,05). У групі IH15 зареєстрували достовірне зменшення кінцевого діастолічного розміру (на 20 %), кінцевого систолічного розміру (на 22 %), збільшення товщини задньої стінки лівого шлуночка (на 44 %), міжшлуночкової перетинки (на 33 %) та збільшення маси лівого шлуночка (на 12 %). Це свідчить про концентричне ремоделювання лівого шлуночка, виникнення якого підтверджене збільшенням індексу відносної товщини стінки на 76 % порівняно з контрольною групою (p < 0,05). На тлі цих змін виявили зменшення кінцевого діастолічного об’єму (на 47 %), кінцевого систолічного об’єму (на 48 %), ударного об’єму (на 49 %) та серцевого викиду (на 50 %) зі збереженою фракцією викиду (p < 0,05). Показники щурів IH60 характеризувалися збільшенням міжшлуночкової перетинки (на 33 %), задньої стінки лівого шлуночка (на 17 %) і збільшенням маси лівого шлуночка серця (на 23 %), а індекс відносної товщини стінки лівого шлуночка був більшим, ніж у контролі (на 15 %, p < 0,05). Встановили зниження кінцевого діастолічного об’єму на 9 %, що супроводжувалось збільшенням систолічного об’єму на 24 % (p < 0,05). Серцевий викид також збільшений порівняно з щурами з 15-денною гіпоксією на 58 % зі зниженням фракції викиду на 8 % (p < 0,05). Показники концентрації маркерів групи IH60 перевищували IH15: кардіотрофін-1 – на 39 %, тайтин – 70 %, колаген 1 типу – на 60 %, анексин V – на 130 % (p < 0,05).
Ремоделювання лівого шлуночка в нормотензивних щурів лінії Вістар, які зазнали інтермітуючої гіпоксії різної тривалості
Kolesnyk Yu. M. - ORCID ID: 0000-0002-1556-5085; Kolesnyk M. Yu. - ORCID ID: 0000-0001-7566-1899; Hancheva O. V. - ORCID ID: 0000-0001-7339-7078; Isachenko M. I. - ORCID ID: 0000-0002-3026-1012.
Keywords: myocardial remodeling; left ventricular; markers of myocardial remodeling; cardiotrophin-1; intermittent hypoxic hypoxia; rats; ремоделювання міокарда; лівий шлуночок; маркери ремоделювання міокарда; кардіотрофін-1; переривчаста гіпоксія; щури